Single feed circularly polarized crescent-cut and extended corner square microstrip antennas for wireless biotelemetry - Mehdi Hasan Chowdhury; Quazi Delwar Hossain; Md. Azad Hossain; Ray Chak Chung Cheung (International Journal of Electrical and Computer Engineering (IJECE), 2019)
In this paper, the development of two novel circularly polarized microstrip antennas is thoroughly explained. These antennas are fed by coaxial feeding technique. One of the primary objectives of the proposed work is to tune the antennas to work in ISM band. This frequency band refers to the internationally recognized radio frequency bandwidth which is to be used explicitly for Industrial, Scientific, and Medical applications. Therefore, these antennas would be suitable to use in the field of wireless biotelemetry. Two new antenna design techniques have been introduced to produce circular polarization, and details of these schemes are described. The proposed microstrip antennas are designed and simulated on Advanced Design System (ADS) software. The return loss of the proposed crescent-cut antenna is -19.3 dB at the operating frequency. The extended corner antenna has the return loss of -29.3 dB at the tuned frequency. The simulation results are also presented and discussed.